2013
DOI: 10.1074/jbc.m113.461087
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Role of Pyk2 in Mediating Thromboxane Generation Downstream of Both G12/13 and Integrin αIIbβ3 in Platelets

Abstract: Background: Pyk2 is abundantly expressed in platelets. Results: Pyk2 regulates thromboxane A 2 generation induced by both 2-methylthio-ADP and AYPGKF. Conclusion: Pyk2 is an important functional tyrosine kinase that is activated by both G 12/13 and integrin ␣IIb␤3 in platelets. Significance: Understanding the mechanism of activation of Pyk2 enhances our understanding of the platelet inside-out and outside-in signaling events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Increasing evidence has confirmed that the activation of both CaMKII and Pyk2 are closely related to the functions of integrins in many cell types [26, 27]. We observed that blocking integrin β1 with its functional blocking antibody significantly abrogated phosphorylation of Pyk2 at Tyr 402 and CaMKII at Thr 286 in chondrocytes in the application of periodic mechanical stress.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Increasing evidence has confirmed that the activation of both CaMKII and Pyk2 are closely related to the functions of integrins in many cell types [26, 27]. We observed that blocking integrin β1 with its functional blocking antibody significantly abrogated phosphorylation of Pyk2 at Tyr 402 and CaMKII at Thr 286 in chondrocytes in the application of periodic mechanical stress.…”
Section: Discussionsupporting
confidence: 52%
“…ERK1/2 has been widely reported to be downstream of CaMKII and Pyk2 in many cell types under different conditions, and integrins also appear vital for the activation of CaMKII and Pyk2 in several different settings [24-27]. However, these may not be true for all cells.…”
Section: Introductionmentioning
confidence: 85%
“…and others have also shown that inhibition of either ERK1/2 or Pyk2 activation results in abolition of thromboxane generation in ADP‐stimulated platelets . Previous studies have shown that 2MeSADP‐induced ERK1/2 phosphorylation occurs independently of outside‐in signaling, and that, rather, MEK1/2, SFK and PI3K proteins regulate ERK1/2 activation . Inhibition of MEK1/2 and PI3K with pharmacological inhibitors prevents 2MeSADP‐mediated secondary platelet aggregation by abolishing thromboxane generation, similarly to PDK1 inhibition .…”
Section: Discussionmentioning
confidence: 97%
“…These findings indicate that p38 predominantly drives the phosphorylation of cPLA 2 in platelets. In support of this, a number of studies highlight the presence of other pathways that drive thromboxane production in a p38, ERK1/2, and Pyk2 mutually dependent manner [2] [3, 4]. …”
mentioning
confidence: 99%
“…Based on these new and previously published findings [2] [3, 4] [1], we propose the following model incorporating pathways regulating thromboxane generation by all three protein kinases (ERK1/2, p38, Pyk2), upon 2MesADP stimulation of platelets.…”
mentioning
confidence: 99%